Standar Penilaian Kompetensi Pedagogik Guru Pendidikan Agama Islam di SMA Negeri 1 Tapa - Sitti Masturiwaty Huntojungo (Pascasarjana IAIN Sultan Amai Gorontalo, 2020)
Teacher pedagogic competence has an important role in the quality of learning. Every teacher must be able to master the indicators that exist in pedagogical competence, to achieve the quality of learning. The purpose of this study was to analyze the process of implementing teacher pedagogical competency assessment standards and their impact on the performance of Islamic Religious Education teachers at State Senior High School 1 Tapa. The research method uses descriptive qualitative. Research shows that: 1) the implementation of pedagogical competency assessment standards for Islamic Religious Education teachers has not been carried out by existing indicators. The mismatch was found between the observations of learning and the value of each indicator obtained. Every value from each learning indicator should be an implementation of each learning indicator. 2) there is an overlap in every indicator that exists in other aspects of pedagogical competence, it should be related to each indicator in each aspect. 3) every indicator of pedagogical competence has not been maximally implemented. 4) the impact of the implementation of pedagogical competency assessment standards on the performance of Islamic Religious Education teachers has positive and negative effects both for teachers, students, and schools.